Aortic and supra-aortic arterial tortuosity and access technique: Impact on time to device deployment in stroke thrombectomy. Issue 3 (June 2021) - Rosa, Joao Alves; Roberts, Rachel; Wareham, James; Crossley, Robert; Cox, Anthony; Mortimer, Alex
Background: Longer intervals to reperfusion in patients treated with mechanical thrombectomy (MT) for emergent large vessel occlusion (ELVO) stroke are associated with worse outcomes and influenced by the operator's ability to navigate individual anatomy. Our aims were to assess the impact of time from puncture to first deployment of the MT device (DT) on technical and clinical outcomes, develop an A natomical A s sessment for M echanical T hrombectomy S core (ASMETS) that could predict DT and assess how different methods of intracranial access (coaxial-direct or exchange) influence this. Methods: Retrospective review of a prospective database of patients treated with MT for ELVO between November 2015 and August 2018. CTAs were assessed for ASMETS. Intracranial access technique was at the discretion of the operator. Technical and clinical outcomes and complications were recorded. Linear and logistic regression analysis was performed. Results: 92 patients were included. The impact of DT on clinical outcomes was significant. An unfavourable ASMET score is significantly associated with longer DT (p = 0.002) and linear regression showed DT time can be predicted by ASMETS – F(1, 90) = 6.182, p = 0.015. No difference was demonstrated between different access techniques. Conclusion: CTA-based ASMETS can predict time between arterial puncture and deployment of the mechanical thrombectomy device in stroke patients, irrespective of the technique used to catheterise the target ICA. This could inform the operator in preparing appropriate strategies to overcome challenging vascular anatomy in patients undergoing MT.